Operational data for the risk management of victim operated explosive devices in humanitarian mine action: a practitioner’s perspective - Evans, Roly; Nelson, Liz; Temple, Tracey (Elsevier, 2024)
Since Mine Action's inception at the end of the 1980s, operators have collected limited data on the Victim Operated Explosive Devices (VOEDs) they clear. This includes not only data on the explosive ordnance itself but data on how they were found, where they were found and how they were processed and ultimately destroyed. In a context where detection of mines, boobytraps and certain Victim Operated Improvised Explosive Devices (VOIEDs) is an ongoing humanitarian and military challenge, significantly expanded operational data collection provides an achievable way to facilitate enhanced operational risk management. Risk decisions inherent in the clearance of VOEDs are better if made on the basis of extensive operational data. In the absence of a technological solution to detect and positively discriminate VOEDs from false positive indications, the collection of operational data offers the best prospect for “managing” if not “solving” the problem.
Keywords: Mine action; Victim operated improvised explosive devices (VOIEDs); Anti-personnel mines (APM); Anti-vehicle mines (AVM); Booby-traps; Operational data